A case of spongiform polioencephalomyelopathy in a cat with a history of behavioural problems. Issue 2 (6th August 2015) - Camps, Tomàs; de la Fuente, Cristian; Pumarola, Martí; Amat, Marta; Le Brech, Susana; Manteca, Xavier
A 7-month-old, entire female, domestic shorthair cat was referred to our behavioural service owing to soiling in the house and a play-related problem. The owners' complaints were that the cat had never used the litter tray, and it did not know how to play. After reviewing the behavioural history, a problem of substrate preferences acquisition was suspected with regard to the elimination problem. During the consultation, the physical examination was unremarkable, but the neurological examination revealed a moderate and hypermetric ataxic gait, and a bilateral lack of menace response. Some degree of visual impairment was suspected. The problem was located in the central nervous system (CNS); specifically, an intracranial and multifocal problem was diagnosed. After a complete work-up (complete ophthalmological examination, complete blood count and a complete biochemistry panel, feline immunodeficiency virus/feline leukaemia virus test, thorax radiographs, abdominal ultrasound, brain magnetic resonance imaging [0.2 T], cerebrospinal fluid analysis and a urinary metabolic screen test), a degenerative CNS problem was suspected. No treatment was prescribed for the neurological problem. Regarding the problem of soiling in the house, reward-based training with a clicker was used, and the cat partially improved in a few weeks. Three months later, the cat was referred to the neurology service in status epilepticus. A symptomatic treatment was prescribed, with a mild response. After 2 years of treatment and a progressive worsening, the cat was euthanased. Necropsy revealed spongiform polioencephalomyelopathy. In order to rule out prion aetiology a PrPsc inmunohistochemistry assay was performed, and the results were negative. Congenital spongiform polioencephalomyelopathy (CSP) was diagnosed. We strongly suggest that the cat's behavioural clinical signs were caused by the CSP, causing learning impairment. To the best of our knowledge, this would be the first case in which a congenital degenerative disease affected a cat's capability to learn, leading to behavioural signs as the main complaint of the owners, even before neurological signs are detected by the owners.